INCORPORATION OF FERMENTED DRUMSTICK (MORINGA OLEIFERA) LEAVES FOR GROWTH AND HEALTH OF AMUR CARP (CYPRINUS CARPIO HAEMATOPTERUS) - ACHARYA, PRIYANKA; NANDA, DR SAUMYENDRA; SAHU, DR BRUNDADAN; MAHANTA, DR KEDARNATH; SWAIN, DR BK; UDGATA, DR SANTOSH KUMAR (Journal of the Inland Fisheries Society of India, 2025)
The effect of fermented drumstick (Moringa oleifera) leaves on the growth and health of Amur carp (Cyprinus carpio haematopterus) was studied. Five iso-nitrogenous (CP 34%) and iso-calorie (360 Kcal 100 g-1) diets were formulated. Diet T0 had conventional feed ingredients, while T1, T2, T3 and T4 had fermented moringa leaf powder at 5%, 10%, 15% and 20%, respectively replacing equivalent GNOC. Amur carp fry (1.17±0.05g) were reared in triplicate in 200 l FRP tank with aeration, feeding and siphoning. At the end fishes were challenged with Aeromonas hydrophila. The T4 group had significantly (p<0.05) highest weight gain (513.6%), specific growth rate (2.01), feed efficiency ratio (0.55) and protein efficiency ratio (1.64). A gradual increase in weight gain with increase in the level of fermented moringa leaf powder was noticed, recording a 177% increase in weight gain in T4 compared to T0. After the challenge study, lowest mortality rates (10%) were observed in T3 and T4. Hence, fermented moringa leaf powder can be incorporated up to 20% in Amur carp diets to improve growth, survival and health of the fish.